Playing tag in the dark: diagnosing slowness in library response time. - Brown-Sica M (Information Technology & Libraries, 2008)
In this article the author explores how the systems department at the Auraria Library (which serves more than thirty thousand primarily commuting students at the University of Colorado-Denver, the Metropolitan State College of Denver, and the Community College of Denver) diagnosed and analyzed slow response time when querying proprietary databases. Issues examined include vendor issues, proxy issues, library network hardware, and bandwidth and network traffic.